The social capabilities of biomimetic industrial products and their relationship to aesthetic preference - Tayseer Abdul Karim Abboud; Ali Ghazi Matar (الاكاديمي)
The research tagged with (the social capabilities of the simulated industrial products of the organism and its relationship to aesthetic preference) was concerned with studying the phenomenon of the social capabilities of the simulated products of the organism that affects the role of social capabilities in adding the aesthetic preference dye of the identity of the industrial product for the purpose of meeting and filling the consumer's need, so the research problem is represented by the following question: Are social capabilities related to the aesthetic preference of the mimic industrial product of the organism (robot)? Research is a step to study and define the concept of social capabilities and their relationship to designing the simulated products of the organism. As for the research methodology, it resulted in the selection of the research sample according to its proximity to the study objectives. Products from CEREVO and Keenon contained the year from (2020 to 2023). (5) samples were chosen by a intentional sample of two appropriate models for the research requirements. It contained a description of the models and their analysis and containing the results and conclusions that the researcher leads to, the most important of which are: the aesthetic preferences in the design of the industrial product and their relationship to social capabilities play an essential role in emotional treatment and motivated by aesthetics to form the foundations of an interaction between man and the industrial product through (direction, emotion, complexity).